The influence of dietary immunomodulatory factors on development of food allergy in children - Sardecka, Izabela; Krogulska, Aneta; Toporowska-Kowalska, Ewa (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
In the last few years many studies have been conducted on the role of dietary and environmental factors in the prevention of allergic diseases among children. Many studies have shown that the diet of pregnant women and children in their early postnatal life, rich in antioxidants, vitamin D, and fatty acids is beneficial as it reduces the risk of allergy in their future life. Moreover, there are many reports about the main role of gut microbiota and probiotics in the allergy prevention, what can indicate new ways of procedures in allergic diseases.